A study on human perception in aircraft cabins and its association with volatile organic compounds. (1st July 2022) - Lou, Xinyuan; Sun, Yuexia; Lv, Dachao; Yin, Yihui; Pei, Jingjing; He, Junzhou; Yang, Xudong; Cui, Xikang; Liu, Yingjun; Norback, Dan; Chen, Qingyan
Abstract: More than 8 million people fly on commercial aircraft each day with approximately 5% having a pre-existing respiratory disease. Thus it is necessary to provide high air quality in aircraft to protect public health. Volatile organic compounds (VOCs) present in aircraft cabins are suspected to contribute to the reported complaints. We investigated concentrations of VOCs, air temperature, relative humidity, and CO2 concentrations in a total of 46 flights, including 26 Chinese domestic flights and 20 international flights. We focused on the data from the cruising phase without meal serving in which the air supply and air recirculation were steady. A total of 284 passengers (i.e., 101 on international flights and 183 on Chinese domestic flights) were invited to participate in questionnaire surveys in this phase. We performed a linear mixed model analysis by controlling for potential confounders (age, gender, smoke habits, and history of allergy) to study associations between VOCs exposures and passengers' complaints. Xylene was significantly associated with irritations of the eyes, nose, and throat on both international and domestic flights, with antilog beta values from 1.12 to 1.28 ( p  < 0.05). The association of some aldehydes (i.e., nonanal, decanal, and heptanal), which are potential oxidation products with ozone, with passengers' sensory irritations was also significant, especially during international flights (antilog beta values: 1.19–1.22). It indicates that VOCs, especially xylene and aldehydes, in aircraft cabins may influence the perceived indoor air quality and complaints among passengers. Highlights: We focused on the association of targeted VOCs with subjective perceptions in cabin environment. Higher exposure to toluene was a risk factor for sensory irritation, headache and fatigue. Xylene and ozone-initiated by products were related to sensory irritations among passengers.